(untitled) (Journal of Hama University, 2021)
A woman’s nutritional needs increase during pregnancy to achieve the requirements of the fetus growth and the mother’s tissues associated with pregnancy. Since the nutritional status of a pregnant woman is one of the most important determinants that affect the outcome of pregnancy, Following a proper diet is one of the priorities of the care provided to maintain the health of the mother and the fetus and achieve optimal safe motherhood. The aim of this study was to assess the nutritional status of pregnant women at Tishreen University Hospital in Lattakia. A descriptive cross-sectional study was performed using a convenience sample of 200 pregnant women at Tishreen university Hospital in Lattakia, Syria. Data were collected during the period of April 2019 to March 2020. A structured questionnaire on socio-demographic information was completed, and an assessment scale of 19 items concerning nutritional practice was measured . In addition to, an observation from developed by the researcher. The findings showed that the three quarters of participants visited the gynecological clinic once every month, only a quarter of participants visited the gynecological clinic once every two months. However, That majority of the participants took nutritional supplements (vitamins and minerals) during pregnancy. About three quarters of participants had normal hemoglobin level, while the remaining quarter of participants had anemia. Also, the vast majority of the study participants had normal value of mid-arm circumference according to the scale. This study recommended to conduct nutrition education programs to learn women about the nutritional needs and the elements to be consumed or avoided during pregnancy, In addition, more studies reflecting the nutritional status and health practices of pregnant women should be conducted on the maternal community with a larger sample size.